Research of antimicrobial resistance and its associated genes distribution in Escherichia coli from diarrheic calves in the Ulagai region of China - Gao, Wei; Zhang, Xinying; Sun, Miao; Han, Dongxu; Wang, Jianing; Li, Yue; Sanren,; Yu, Lidong; Gui, Fang; Guo, Lei; Nimalaxi,; Wang, Zi; et al. (Frontiers in Veterinary Science, 2025)
As a conditional pathogenic bacterium, Escherichia coli is a major contributor to infect calf diarrhea. It has attracted extensive attention due to antimicrobial resistance (AMR) and pathogenicity. To elucidate the AMR profiles and resistance-related genes in E. coli isolated from calf diarrhea samples in the Ulagai region E. coli was isolated and identified from samples of calf feces using E. coli chromogenic medium, Gram staining, and 16S rRNA sequencing. The antimicrobial susceptibility was tested using the Kirby-Bauer disk diffusion method. Resistance genes were analyzed using PCR. Additionally, strains showing severe multidrug resistance were selected for whole-genome sequencing. Multidrug resistance was observed in all 50 isolated E. coli strains. They were resistant to bacitracin, and 82% were resistant to gentamicin. Strains 24, 27, 36, and 15 exhibited particularly high levels of resistance. Analysis of resistance-related genes detected over 90% resistance associated with TEM-1 and tetR and over 80% for CTXM-55, QacH, strB, and floR, sul2 was observed in 100% of the isolates. Four strains indicated genome sizes of 5,144,828 bp, 4,798,224 bp, 4,813,249 bp, and 5,450,201 bp, respectively, harboring 5, 3, 6, and 2 plasmids. Prediction of antibiotic resistance genes revealed that the isolates contained numerous resistance genes, strain 27 carried the highest number (148 in total). All strains isolated from diarrheic calves exhibited multidrug resistance and carried numerous resistance genes. Furthermore, the observation of abundant mobile genetic elements in the strains increases the risk of horizontal gene transfer of resistance genes, indicating the severity of issues faced by clinical prevention and control measures.